Systematic Search and Evaluation of mobile Apps for Wound Care Available in French-Language in Canada - Gagnon, Julie; Chartrand, Julie; Probst, Sebastian; Maillet, Éric; Reynolds, Emily; Chaplain, Valérie; St-Jean, Heidi; East, Raphaelle; Lalonde, Michelle (Canadian Journal of Nursing Research, 2025)
Background Wounds are a significant national health concern, impacting individuals, healthcare systems, and the environment. Despite efforts by organizations to promote evidence-based practices, gaps persist between theory and nurse practice in wound care. Mobile apps show promises in enhancing wound care delivery, but their rapid evolution, including adaptations into different languages such as French, raises concerns about reliability and regulation. Evaluating these apps is crucial for ensuring patient safety and effective wound management. Purpose To review and assess mobile wound care apps available in French for healthcare providers in Canada. Methods A systematic search was conducted across the literature and the two main Canadian online app stores (App Store and Google Play). The included mobile apps underwent quality evaluation using the user version of the Mobile Application Rating Scale (uMARS). Results The initial search retrieved 1,550 apps, of which 260 were screened and 5 included. Included apps were from France and were available on both stores. These apps varied in features, including wound dressing directory ( n = 3), best practices reminders ( n = 2), photography management and digital wound tracking ( n = 1), and total body surface area calculator ( n = 1). Evaluation using uMARS indicated total averages range from 3.52/5 to 4.10/5. The results offer scant insight into the design and evaluation of the apps included. Conclusions The study highlights the need for development and validation of a French wound care app tailored to Canadian healthcare contexts and best practice recommendations, emphasizing collaboration among nurses and stakeholders in technology enhancement for the benefit of Canadians’ health.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance: Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective : To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures: Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care. Main Outcomes and Measures MACEs within 5 years of survey completion. Results : Among the 124 583 patients included in this study, 114 239 (91.7%) spoke English, 4790 (3.8%) spoke French, 325 (0.3%) spoke an Indigenous language, and 5229 (4.2%) spoke an allophone (ie, other) language. The mean (SD) age of the cohort was 63.7 (14.8) years; 57.1% of the patients reported their sex as female. Very few respondents who spoke an Indigenous language at home (<4.6%) received language-concordant care. For French-speaking patients, there was no statistically significant difference in the risk of MACE between those who received language-concordant care and those who received language-discordant care (hazard ratio [HR], 1.09; 95% CI, 0.86-1.36). Allophone-speaking patients who received language-concordant care were 36% less likely to experience MACE (HR, 0.64; 95% CI, 0.51–0.80) compared with allophone-speaking patients who received language-discordant care. Conclusions and Relevance: This retrospective cohort study found large disparities in both access to language-concordant care and risk of MACEs. These findings suggest that language-concordant care could potentially improve the health of individuals in minority language communities.